2002
DOI: 10.1038/sj.bjc.6600370
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and lung cancer in women

Abstract: The association between aspirin use and lung cancer risk in women was examined in a case -control study nested in the New York University Women's Health Study, a large cohort in New York. Case subjects were all the 81 incident lung cancer cases who had provided information about aspirin use at enrollment and during the 1994 -1996 follow up. Ten controls per case were randomly selected from among study participants who matched a case by age, menopausal status, and dates of enrollment and follow-up. Relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 27 publications
3
59
1
1
Order By: Relevance
“…Overall, we found moderate increased risks of cancers of the prostate and kidney. We did not confirm a reduced risk of lung or breast cancer as reported in some studies (Schreinemachers and Everson, 1994;Harris et al, 1996Harris et al, , 1999Akhmedkhanov et al, 2002). Finally, our data support a reduced risk for ovarian cancer, which has also been reported among both users of paracetamol and aspirin (Cramer et al, 1998;Akhmedkhanov et al, 2001), and we observed a reduced risk of cervical cancer, although not among those with 10 or more prescriptions.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Overall, we found moderate increased risks of cancers of the prostate and kidney. We did not confirm a reduced risk of lung or breast cancer as reported in some studies (Schreinemachers and Everson, 1994;Harris et al, 1996Harris et al, , 1999Akhmedkhanov et al, 2002). Finally, our data support a reduced risk for ovarian cancer, which has also been reported among both users of paracetamol and aspirin (Cramer et al, 1998;Akhmedkhanov et al, 2001), and we observed a reduced risk of cervical cancer, although not among those with 10 or more prescriptions.…”
Section: Discussioncontrasting
confidence: 78%
“…Two case -control studies (Rosenberg, 1995;Langman et al, 2000) reported no association between NSAIDs and lung cancer, but a third found a relative risk of 0.7 (95% CI 0.3 -1.3) among women taking aspirin for at least 6 months (Akhmedkhanov et al, 2002). We had no information on cigarette smoking in our population, and thus we cannot rule out that the small SIR elevations for lung cancer (similar in men and women) may be because of differential smoking rates among NSAID users.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) used in relation to lung cancer have been investigated in at least 20 studies, including four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002;Muscat et al, 2003), fourteen cohort studies (Paganini-Hill et al, 1989;Thun et al, 1993;Schreinemachers and Everson, 1994;Langman et al, 2000;Akhmedkhanov et al, 2002;Friis et al, 2003;Holick et al, 2003;Sørensen et al, 2003;Ratnasinghe et al, 2004;Skriver et al, 2005;Hayes et al, 2006;Hernández-Diaz and Rodriguez, 2007;Jacobs et al, 2007;Wall et al, 2007) and three randomised trials (Peto et al, 1988;Lee et al, 1995;Cook et al, 2007). Significantly decreased risks were observed in three of the four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002), although all were based on selfreported drug use after diagnosis of cancer, raising the possibility of recall bias.…”
mentioning
confidence: 99%
“…These include residual confounding due to broad categories of smoking habits (Paganini-Hill et al, 1989;Schreinemachers and Everson, 1994;Langman et al, 2000;Akhmedkhanov et al, 2002;Moysich et al, 2002); misclassification due to a single assessment of aspirin use (Paganini-Hill et al, 1989;Schreinemachers and Everson, 1994;Harris et al, 2002); and small number of lung cancer cases observed (Peto et al, 1988;PaganiniHill et al, 1989;Schreinemachers and Everson, 1994;Akhmedkhanov et al, 2002).…”
mentioning
confidence: 99%